New Lithiated NASICON-Type Li[sub 2]Ni[sub 2](MoO[sub 4])[sub 3] for Rechargeable Lithium Batteries - Begam, K. M.; Michael, M. S.; Taufiq-Yap, Y. H.; Prabaharan, S. R. S. (2004)
We report on the first synthesis of a new NASICON framework Li(2)Ni(2)(MoO(4))(3) and on the investigation of its electrochemical behavior upon Li extraction coupled with structural analysis. Li(2)Ni(2)( MoO(4))(3) was synthesized by a novel soft-combustion approach involving glycine as a combustion agent and the product was found to crystallize in an orthorhombic structure (space group Pmcn) with lattice parameters alpha = 10.424(4) Angstrom, b = 17.525(1) Angstrom, and c = 5.074(3) Angstrom. Reversible extraction and insertion of lithium from and into the framework structure delivered a reversible capacity of similar to115 mAh/g (4.9-1.5 V window) after the first charge/discharge cycle. (C) 2004 The Electrochemical Society.